Preparation of transmission electron microscopy cross-section specimens of crack tips using focused ion beam milling. - Huang, Y; Lozano-Perez, S; Langford, R; Titchmarsh, J; Jenkins, M (2002)
The preparation of transmission electron microscope (TEM) thin foil specimens from metal alloys containing cracks is usually thwarted by the difficulty in preventing preferential erosion of material along the flanks and at the tips of cracks. Recent developments in focused ion beam (FIB) micromachining methods have the potential to overcome this inherent problem. In this article we describe the development of new procedures, one using FIB alone and the other using a combination of FIB with more conventional ion milling to generate TEM specimens that largely retain the microstructural information at stress corrosion cracks in austentic alloys. Examples of corrosion product phase identification and interfacial segregation are included to verify that detailed information is not destroyed by ion bombardment during specimen preparation.